2022
DOI: 10.1002/mrd.23571
|View full text |Cite
|
Sign up to set email alerts
|

Feeding the modern sow to sustain high productivity

Abstract: Selection for hyper-prolific sows has increased the litter size by more than 50% during the last three decades, and proper nutrition of the female pigs has concomitantly changed due to improved prolificacy and productivity of gilts and sows. This review summarizes the physiological characteristics and nutritional challenges associated with feeding modern hyper-prolific sows during the gilt rearing period and during gestation, transition, and lactation periods. The review presents up-to-date knowledge of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 139 publications
(145 reference statements)
1
7
0
1
Order By: Relevance
“…Ability to produce colostrum and milk are some of the most important performance traits for lactating sows to ensure the survival of their piglets 1 , 2 . The main composition of sow colostrum and milk includes fat, proteins, lactose, vitamins, minerals as well as a series of immunoglobulins, which provide a good source of nutrients and passive immunity that support the growth and survival of piglets 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Ability to produce colostrum and milk are some of the most important performance traits for lactating sows to ensure the survival of their piglets 1 , 2 . The main composition of sow colostrum and milk includes fat, proteins, lactose, vitamins, minerals as well as a series of immunoglobulins, which provide a good source of nutrients and passive immunity that support the growth and survival of piglets 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The current study showed that there were no significant differences in BW and BW changes by Se sources or levels, which matched previous studies. Backfat (BF) thickness is a significant parameter to evaluate fat storage in sows, and the change in BF thickness had a high c orrelation with sow BW loss and feed intake during the lactation period [19]. Mahan et al [20] reported that short-term feeding of either Se source at 0.15 or 0.30 ppm Se did not affect BF changes and feed consumption in lactating sows.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to a 200 kg sow and a 300 kg sow, this means that the 300 kg sow has 50% more body mass, but only 35 % more heat production. This statement probably applies even more strongly today because, due to increased fertility performance, feed intake has increased in recent decades, especially during lactation (57). For this reason, large animals must consume less feed per kg of body mass than small animals; therefore, perhaps less metabolic heat is produced from feed intake.…”
Section: Infrared Thermography and Rectal Temperaturementioning
confidence: 99%